(untitled) (Journal of Insurance Studies in South Asia, 2024)
Insurance services are now being integrated into wider financial industry and the insurance sector plays an important role in service-based economy of Nepal. This study examines the factors affecting financial performance of life insurance in the context of Nepalese insurance companies. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are liquidity, leverage, firm age and firm size. The study is based on secondary data of 5 insurance companies with 25 observations for the period from 2073/74 to 2077/78. The data is collected from the reports published by Beema Samiti and Annual Reports of selected life insurance companies. The regression models are estimated to test the factor affecting the financial performance of Nepalese life insurance companies. The study showed that firm size has a positive impact on return on equity and negative impact on return on assets. It indicates that larger firm size leads to decrease in return on assets and increase in return on equity. Likewise, leverage has a positive impact on return on assets and negative impact on return on equity. It indicates that higher the leverage, higher would be the return on assets and lower will be return on equity. Moreover, firm age has a positive impact on return on equity and negative impact on return on assets. It indicates that an increase in firm age leads to increase in return on equity and decrease in return on assets. Moreover, liquidity has a negative impact on return of assets and return on equity. It means that higher the assets liquidity, the lower will would be the return of assets and return on equity. Likewise, there is a negative impact of leverage ratio on return on equity and positive impact on return on assets. It means that an increase in liquidity ratio leads to increase in return on assets and decrease in return on equity.